2014
DOI: 10.1136/bmjopen-2013-003947
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study ofMycoplasma genitaliuminfection and correlates in women undergoing population-based screening or clinic-based testing forChlamydiainfection in London

Abstract: ObjectiveTo determine Mycoplasma genitalium infection and correlates among young women undergoing population-based screening or clinic-based testing for Chlamydia infection.DesignCross-sectional study.SettingNational Chlamydia Screening Programme (NCSP) and two London sexually transmitted infection (STI) clinics.Participants2441 women aged 15–64 years who participated in the NCSP and 2172 women who attended two London STI clinics over a 4-month period in 2009.Outcome measures(1) M genitalium prevalence in defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 40 publications
4
17
0
1
Order By: Relevance
“…The risk factors that are confirmed to be associated with M. genitalium infection from this study included: family type (single and serial monogamy) and multiple sexual partners in which the respondents have more than one lifetime sex partners and/or have husbands who equally have other sexual partners thus corroborating the findings of previous studies (4,(24)(25)(26)(27)(28). Thurman and his co-workers reported that M. genitalium was detected in 9.5% and 10.6% of women and men in heterosexual relationships reporting to an STI clinic (27).…”
Section: Discussionsupporting
confidence: 89%
“…The risk factors that are confirmed to be associated with M. genitalium infection from this study included: family type (single and serial monogamy) and multiple sexual partners in which the respondents have more than one lifetime sex partners and/or have husbands who equally have other sexual partners thus corroborating the findings of previous studies (4,(24)(25)(26)(27)(28). Thurman and his co-workers reported that M. genitalium was detected in 9.5% and 10.6% of women and men in heterosexual relationships reporting to an STI clinic (27).…”
Section: Discussionsupporting
confidence: 89%
“… 9 London Chlamydia Screening Programme 15–24 1017 Cervical/ vaginal swab 4.1% (3.0–5.5) See above Svenstrup et al. 9 Denmark Chlamydia Screening Programme 21–23 921 Vulvo-vaginal swab 2.3% (1.3–3.2) > 10 lifetime partners, ≥ 2 partners in the past year, shorter duration of steady relationship, partner with symptoms Andersen et al. 6 Australia General practice 15–25 1116 Vulvo-vaginal swab 1.6% (0.7–2.6) Indigenous status, ≥ 2 partners in the past year, ≥ 3 partners in the past year without condoms Walker et al.…”
Section: Introductionmentioning
confidence: 99%
“…Además, la co-infección entre C. trachomatis y especies de Mycoplasma o Ureaplasma ha sido reportada en pacientes con VIH 33 y en mujeres de 15 a 64 años de edad, que muestran infecciones genitales hasta en el 9% de los casos 34 . De manera similar, se ha reportado la co-infección entre Chlamydia pneumoniae y Mycoplasma pneumoniae en infecciones de vías respiratorias en niños menores de 15 años 35 .…”
Section: Discussionunclassified